Structural observations on spermatogenic cells of Japanese quail (Coturnix coturnix japonica) pre-pubertally exposed to dibutyl phthalate: A light and transmission electron microscopy study. (January 2022) - Zakariah, Musa; Molele, Reneilwe A.; Mahdy, Mohammed A.A.; Ibrahim, Mohammed I.A.; McGaw, Lyndy J.
Graphical abstract: Highlights: Dibutyl Phthalate (DBP) induces germ cell degenerations in the testis of the Japanese quail. Spermatogenic cells of the Japanese quail seem/appear to be more sensitive to DBP. Electron microscopy is a sensitive technique in evaluating germ cells. DBP is a potent disruptor of spermatogenesis in the quail. Only spermatids were recognized in the high dose of the DBP treated group. Abstract: Exposure to dibutyl phthalate (DBP) induces testicular damage in mammals. However, studies on the effects of DBP on spermatogenic cells in birds are grossly lacking. Therefore, this study was designed to determine the effects of the pre-pubertal exposure to DBP on the histology and ultrastructure of spermatogenic cells in the testis of adult Japanese quail ( Coturnix coturnix japonica ). The birds were randomly divided into five dosage groups at the age of 4 weeks. The control group received a corn oil vehicle only (a dose of 1 mL/kg body weight), while the other four experimental groups received a daily dosage of 10, 50, 200, 400 mg/kg body weight of DBP (dissolved in corn oil), respectively with the aid of gastric lavage, for 30 days. Testicular samples were processed and examined by light microscopy and transmission electron microscopy. Histopathological evaluation revealed vacuole formation, germ cell degenerations, and the absence of spermatogenic cell series. Ultrastructurally, chromatin clumps in spermatocyte and degenerated spermatogonia with ruptured nuclear membranes resting on the distorted basement membranes were observed. Others were intracytoplasmic vacuoles in round spermatids and fragments of dense apoptotic bodies. In conclusion, the findings of the present study reveal that spermatogenic cells of Japanese quails seem to be more sensitive to DBP-induced degeneration compared to mammalian species studied. The Japanese quail could be used to monitor environmental contamination with low doses of DBP.